Pengembangan Media Pembelajaran Inovatif untuk Menstimulasi Keterampilan Gerak Lokomotor Anak Usia 5-6 Tahun - Julianti, Hani; Nurani, Yuliani; Pratiwi, Niken (Indonesian Journal Publisher, 2024)
This study aims to develop innovative learning media to stimulate locomotor skills in children aged 5-6 years. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Questionnaires are used as instruments for expert reviews, and one-on-one evaluation tools are used for children aged 5-6 years. The results of the product's validity test by content experts obtained a final score of 98.2%. The validity test results by media experts received a final score of 93.7%. The product testing on children aged 5-6 years resulted in a final score of 91.6%. The research findings indicate that the innovative learning media named